The Effect of Product Quality and Price on Consumer Satisfaction at Kopi Jago, with Customer Retention as a Moderating Factor (Case Study: Kopi Jago Touring Sunter Lake) - Nathadiharja, Sri Sukartono; Ivada, Tia; Soetiyani, Ari (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study investigates how Product Quality and Price affect Consumer Satisfaction at Kopi Jago Keliling Danau Sunter, while also examining the moderating role of Customer Retention. Using a sample of 150 respondents and analyzed through SmartPLS (Partial Least Square) with a causal research design, the study tested both direct and moderating effects. The findings reveal several key points. First, Product Quality significantly influences Consumer Satisfaction, confirming that aspects such as product appearance, taste, texture, and uniqueness enhance customer experiences. Second, Price also has a significant effect, showing that affordability, competitiveness, and perceived value contribute to satisfaction. Third, Customer Retention strongly impacts Consumer Satisfaction, as indicators like revisiting interest, repeat purchases, recommendations, and loyalty reinforce positive consumer experiences. Fourth, Customer Retention moderates the relationship between Product Quality and Consumer Satisfaction positively, strengthening the effect. However, fifth, Customer Retention does not moderate the relationship between Price and Consumer Satisfaction, meaning price remains a direct driver rather than a moderated one. Overall, the study highlights that improving product quality, setting appropriate pricing, and fostering customer retention are crucial strategies for enhancing satisfaction and sustaining long-term customer relationships.